Competencias docentes en Educación Infantil e inclusión educativa: Diseño y validación de un cuestionario (2020)
The teaching community in Early Childhood Education represents a key element to promote an inclusive education and to identify what competences must be acquired in their initial training. The objective of this paper is to show the design and validation process of a questionnaire aimed at learning the competences which must be present in the degree in Early Childhood Education at the University of El Bosque (Bogotá, Colombia). There has been a sample of 158 participants: 7 judges, 92 students, 35 graduates and 24 employers. The instrument elaborated is made up of 53 items distributed in four dimensions - scientific, social, methodological and personal competences. The procedure has complied with the following phases: 1) revision of the state of art and initial elaboration of the questionnaire; 2) content validity through the expert judgement technique and introduction of the necessary changes; 3) instrument implementation; 4) analysis of the statistical reliability. The results show that the CEINCLUSIVA questionnaire is a valid and reliable instrument with a Cronbach's alpha of.964. for all items. These positive results recur in every dimension of the instrument elaborated. Likewise, the judges' agreement relating to the pertinence, relevance, clarity and exclusivity of the proposed items stands out.